1980
DOI: 10.1111/j.1365-2222.1980.tb02123.x
|View full text |Cite
|
Sign up to set email alerts
|

Circulating immune complexes in bronchial asthma

Abstract: Summary Soluble immune complexes were detected by a solid phase Clq binding assay in forty‐two out of 106 well studied asthmatic patients (39.6%) and in eleven out of 145 age‐matched controls (8%; P < 0.01). Clinical significance of immune complexes has been evaluated by comparing the following parameters in patients with and without such complexes: age, sex, duration of disease, IgE‐mediated allergy (RAST, skin test), precipitins (Aspergillus, Candida albicans, Thermoactinomycetes), corticodependency, lung fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

1981
1981
1989
1989

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 22 publications
0
7
1
Order By: Relevance
“…Increased levels of circulating immune complexes (CIC) have recently been reported in various atopic conditions such as rhinitis [3], eczema [12] and asthma [15]. These findings are, however, in conflict with those of others who failed to detect increased levels of CIC in atopy [6].…”
Section: Introductioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Increased levels of circulating immune complexes (CIC) have recently been reported in various atopic conditions such as rhinitis [3], eczema [12] and asthma [15]. These findings are, however, in conflict with those of others who failed to detect increased levels of CIC in atopy [6].…”
Section: Introductioncontrasting
confidence: 55%
“…Some previous studies have demonstrated CIC in atopy [3,12,15] while others have failed to do so [6], This sort of conflict is not uncommon and it is now widely recognised that each in vitro assay for CIC will detect only a restricted type of complex [8]. The EArosette inhibition assay can detect IgG-containing im mune complexes which have the capacity to react with human lymphocytes possessing cell surface receptors for the reacted Fc of IgG, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…{\97S) found no evidence of circulating immune complex (IC) in patients with rhinitis and asthma who received subcutaneous injections of mould house-dust mite and pollen extracts. In contrast, Stendardi, Delespesse and Debisschop (1980) reported that about 40% of patients, who were hyposensitized with different allergens, developed detectable IC in serum simultaneously with a rise in PSA-most common in patients immunized with mould extracts, and Cano et al (1977) found that atopic patients compared to normal subjects had significantly higher values of circulating IC. The highest mean-values were seen in patients who had been on long-term immunotherapy.…”
Section: Discussionmentioning
confidence: 96%
“…Girard, De Wurstemberger and Fernandes (1978) demonstrated IC by Ci,, binding assay in peripheral blood in 86-6% of seventy-one patients with clinical and laboratory evidence of allergic alveolitis; however, they found these IC also in about 25% ofthe asymptomatic exposed subjects and in 7-6% ofthe healthy controls. Stendardi (1980) and Massai et al (1981) demonstrated soluble IC by a solid-phase Ciq binding assay in asthmatic patients (39-6% and 6-4% respectively) and in healthy subjects (8% and 7 9%, respectively). In active sarcoidosis the IC reported ranges from 23% (Hedfors & Nordberg, 1974, platelet aggregation assay) to 58% (Johnson et ai, 1980, Ciq binding assay).…”
Section: Discussionmentioning
confidence: 98%
“…Immunocomplexes (IC) have been demonstrated in biopsy material (Wenzel, Emanuel & Gray, 1971;Ghose, Landrigan & Asif, 1974) and in the peripheral blood (Ghose, Landrigan & Asif, 1974;Geha, 1977;Girard, De Wurstenberger & Fernandes, 1978); IC, however, are also present in asymptomatic exposed subjects (Girard, De Wurstemberger & Fernandes, 1978) and in other bronchopulmonary syndromes (Stendardi, Delespesse & Debisschop, 1980;Dresin, 1981).…”
Section: Introductionmentioning
confidence: 99%